THE EFFECT OF PRIMARY AND REPEATED CESAREAN BIRTH ON BREASTFEEDING SUCCESS AND MATERNAL ATTACHMENT LEVEL IN POSTPARTUM: A CROSS-SECTIONAL AND COMPARATIVE STUDY - Yilmaz, Ayşe Nur; Altiparmak, Sümeyye; Aksoy Derya, Yeşim (Inonu University, 2024)
This research was conducted to determine the effect of primary and repeated cesarean births on breastfeeding success and maternal attachment level in postpartum women. The cross-sectional and comparative study sample consisted of 322 postpartum women who applied to a public hospital in eastern Turkey. Data were collected with the "Personal Information Form", "LATCH Breastfeeding Assessment Tool" and “Maternal Attachment Scale(MAS)". Descriptive statistics, independent group’s t-test, and Pearson correlation analysis were used to analyze the data. The average age of the puerperants with primary and repeat births was determined as 28.14±6.15, and 30.56±4.91, respectively. The mean LATCH and MAS total scores of postpartum women who had primary cesarean delivery were lower than those of postpartum women who had repeated cesarean delivery, and the difference between them was statistically significant(p=0.000). It was found that there was a weak, positive relationship between the MAS and LATCH score averages of women who had primary and repeated cesarean deliveries, and as breastfeeding success increased, the level of attachment also increased. It was concluded that breastfeeding success and attachment levels were lower in primary cesarean births compared to repeated cesarean births, and as the breastfeeding success achieved in both groups increased, the level of attachment increased. © 2024, Inonu University. All rights reserved.
Primer ve Mükerrer Sezaryen Doğum Yapmanın Lohusalardaki Emzirme Başarısı ve Maternal Bağlanma Düzeyine Etkisi: Kesitsel ve Karşılaştırmalı Bir Çalışma
Keywords: Attachment; Breastfeeding success; Postpartum; Primary cesarean; Repeated cesarean